Knowledge Transfer in Online Meat and Dairy Goat Certification Programs in English and Spanish. (7th May 2021) - Gipson, Terry A; Merkel, Roger C; Rodriguez, Abner; Fernandez, John
Abstract: In 2020, on-line courses in Spanish (SP) for dairy (D) and meat (M) goat producers were unveiled (http://certification.goats.langston.edu ). These courses complemented the existing courses in English (EN) for D and M. Thirty-one undergraduate and one graduate animal science students at the University of Puerto Rico (UPR), Mayagüez enrolled in the SP courses for beta-testing. Nineteen students completed D-SP, 9 completed M-SP, and 4 completed both. Participants take a pre-test (PRE) and if the PRE score < 85%, a post-test (POST) is required. To complete D, passing scores are required on 18 required modules and 7 of 10 electives. To complete M, passing scores are required on 21 required modules and 9 of 12 electives. A random sample of previous participants (23 D-EN and 13 M-EN) in the same time length (86 ± 18.2 d) was added to the UPR dataset. The objective of this study is to evaluate the difference (DIFF) between PRE and POST scores as a measure of knowledge transfer. Mixed model analysis was conducted with the dependent variable of DIFF, the independent variables of course (D or M), language (EN or SP), the two-way interaction, and participant as the random effect. There were significant course (P > 0.01) and language (P > 0.05) effects on DIFF. M had lower DIFF than D (29.0% vs 34.1%) and EN had lower DIFF than SP (29.2% vs 34.0%). When required module within course (18 for D and 21 for M) was added to the model to examine specific module differences, there was a significant course(module)*language interaction (P > 0.01) with values ranging from 15.6% for Preventive Herd Health in EN M to 45.1% for Milking Systems in SP D. Participant background and language may play a role in knowledge transfer for online courses; however, a larger sample would be needed to confirm this hypothesis.